PENINGKATAN HASIL BELAJAR LEMPAR TANGKAP SISWA SEKOLAH DASAR DENGAN MODIFIKASI PERMAINAN BEREGU (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
This study aims to improve learning outcomes throwing catch on third-grade students of SDN 03 BatangPurbo. Modification used is Team game. Results showed that pre-cycle mastery learning the material caughtthrowing KKM is less than 70 it is in tujukkan of results pre-cycle value is the average value of 60 and onlyachieve mastery 28% of the total number of students is 14. Having applied the method on a cycle Team game1, an increase in the average value is 73 and the completeness reaches 64% of the total number of students thatmeet the initial target completeness 14.untuk 100% then proceed to cycle 2 to further enhance students' masterylearning while using a modification of the game Team completeness result 86 % and the average score ofstudents to 84. Conclusions This study suggests that modification Team games can improve learning outcomesthrowing catch on third-grade students of SDN Purbo 03.